2015
DOI: 10.1016/j.sbspro.2015.03.360
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Anxiety of Male and Female Iranian EFL Learners on their Writing Performance

Abstract: In an attempt to delve into the issue of affective variables related to language learning, the present study focuses on the relationship between anxiety and writing performance across Iranian EFL learners with the effect of gender. To do so, Second Language Writing Anxiety Inventory (SLWAI) developed by Cheng (2004) and writing performance test were applied to collect the data. 45 EFL learners were invited to participate in this study. T-test analysis revealed that significant difference was found in level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
7
20
2
Order By: Relevance
“…doubting about the topic or the requirements of the task, thinking about how to organize their ideas, and having their minds going blank-, they dealt with them more calmly, with more confidence, and worrying less than lowlevel writers. These findings are consistent with the majority of the literature, which correlates a lower level of anxiety with a better writing performance (Lee and Krashen 2002;Huwari and Aziz 2011;Martinez et al 2011;Kara 2013;Meng and Tseng 2013;Jebreil et al 2014;Liu and Ni 2015;Stewart et al 2015;Ho 2016), but contrast with Entwistle and McCune (2004), who link writing anxiety with high academic performance. Likewise, the causes for participants' writing anxiety commented above are parallel to those described by Liu and Ni (2015) in their study on EFL Chinese university students.…”
Section: Writing Anxietysupporting
confidence: 91%
See 2 more Smart Citations
“…doubting about the topic or the requirements of the task, thinking about how to organize their ideas, and having their minds going blank-, they dealt with them more calmly, with more confidence, and worrying less than lowlevel writers. These findings are consistent with the majority of the literature, which correlates a lower level of anxiety with a better writing performance (Lee and Krashen 2002;Huwari and Aziz 2011;Martinez et al 2011;Kara 2013;Meng and Tseng 2013;Jebreil et al 2014;Liu and Ni 2015;Stewart et al 2015;Ho 2016), but contrast with Entwistle and McCune (2004), who link writing anxiety with high academic performance. Likewise, the causes for participants' writing anxiety commented above are parallel to those described by Liu and Ni (2015) in their study on EFL Chinese university students.…”
Section: Writing Anxietysupporting
confidence: 91%
“…These two issues have been commonly studied in isolation, but there is also research on the connection between emotional constructs and the final written outcome (Karakaya and Ülper 2011;Jebreil et al 2014;Kirmizi and Kirmizi 2015;Liu and Ni 2015;Ho 2016).…”
Section: Metacognitive Writing Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies were interested in exploring Foreign Language Anxiety (FLA) to the core skills in English language acquisition. First study comes from Jebreil et al (2015) where they investigate about the effect of gender aspect to Iranian writing's performance. As a result, they found that there is a significant different between males and female students' writing production in terms of grammar and punctuation.…”
Section: A Introductionmentioning
confidence: 99%
“…Jebreil, Azizifar, & Gowhary (2015) found male participants in their study might experience relatively greater amount of cognitive anxiety than female participants, especially in grammar and punctuation. On the contrary, Kırmızı & Kırmız (2015) found the male students in their study suffered less from writing anxiety because they had higher levels of writing self-efficacy.…”
Section: Causes Of Writing Anxietymentioning
confidence: 67%